PERAN DENSUS 88 ANTI TEROR POLRI DALAM DERADIKALISASI NARAPIDANA TERORISME DAN MANTAN NARAPIDANA TERORISME DI WILAYAH HUKUM JAWA TENGAH SEBAGAI UPAYA PENEGAKAN HUKUM - Mahfud Suwono Jati; Ishviati Joenaini Koenti; Sigit Setyadi (Universitas Janabadra, 2018)
Terrorism is considered extraordinary crime, therefore, Indonesian government issued Law No. 15 of 2003 and Law No. 9 of 2013 and formed Detachment 88 Anti-Terror Unit. Terrorism is driven on the basis of ideology so that Densus 88 AT employs de-radicalization in handling the terrorists and former terrorists. De radicalization aims to change radical ideology. Most of the terrorists and former terrorists who have been deradicalized do not change their radical ideologies easily. The former terrorists instead commit to terrorism over and over again by recruiting new members found in correctional institutions. This is juridical empirical research based on social issues. The research specification is analytical descriptive research. The primary data was taken from an interview with de-radicalization officers in the police headquarters. Meanwhile, the secondary data was taken from literature study. The data collection was conducted by applying field research, literature, and interviews. The data analysis employs qualitative descriptive method.The study results the following conclusions: The role of Densus 88 AT in de radicalization of terrorists and former terrorists in Central Java used identification, re-socialization, reeducation and monitoring; The obstacles encountered by Densus 88 AT were that there was no law regulating the de-radicalization so that the terrorists and former terrorists were not obliged to follow the de-radicalization, the number of the de-radicalization officers was not balanced with that of the terrorists and former terrorists and not all of the officers joined the de-radicalization training, the correctional institution for the terrorists was not separated from that for the famous criminals, accordingly they potentially taught radical doctrines to the famous criminals, the views and attitudes of the society despising the former terrorists’ relatives make them rejoin terrorist networks.